KAJIAN LANSKAP BUDAYA SUKU BOTI DI KABUPATEN TIMOR TENGAH SELATAN-NTT - Nubatonis, Wardy; Setyabudi, Irawan; Hamzah, Amir (Universitas Tribhuwana Tunggadewi, 2019)
Indonesia's current Culture and Landscape is a combination of various diverse interactions of natural, cultural and historical heritage. The formation of this diversity is not only from the local or national cultural sense, but also from the dynamic instruction of various ethnic immigrants from various countries who bring their respective cultural trends. The formation of this diversity is not only from the local or national cultural sense, but also from the dynamic instruction of various ethnic immigrants from various countries that bring their respective cultural trends. The method used in this research is Qualitative and Quantitative Methods where the purpose of this method is in-depth understanding of a problem being studied. Based on the results of processing expert respondent data, it was found that the highest priority or highest alternative recommendation for developing the Boti landscape was preservation and the lowest priority rating was conservation The physical characteristics of the Boti tribe include the architecture of traditional houses, the use of customary lands, places of worship, land use. Cultural characteristics of the Boti tribe landscape consist of the population of the Boti tribe villagers in Kie District, Timor Tengah Selatan Regency - NTT The recommendation for tourism development in the Boti tribal region is preservation. Budaya dan Lanskap Indonesia saat ini adalah gabungan dari berbagai interaksi warisan alam, budaya, dan sejarah yang sangat beragam. Pembentuk keragaman ini tidak hanya dari akal budaya lokal atau nasional, tetapi juga dari dinamisnya instruksi beragam etnis pendatang dari berbagai negara yang membawa trend budayanya masing- masing. Tujuannya adalah mengidentifikasi kondisi fisik budaya suku Boti dalam kaitanya dengan arsitektur dan lanskapnya dan kajian lanskap budaya suku Boti di Kabupaten Timor Tengah Selatan. Metode yang digunakan dalam penelitian ini adalah Metode Kualitatif dan Kuantitatif dimana tujuan dari metode ini adalah pemahaman secara mendalam terhadap suatu permasalahan yang sedang dikaji. Berdasarkan hasil pengolahan data responden ahli diperoleh bahwa prioritas utama atau tertinggi alternatif rekomendasi pengembangan lanskap suku boti adalah preservasi dan peringkat prioritas terendah adalah konservasi Karakteristik fisik lanskap suku boti meliputi keadaan .arsitektur rumah adat, tata guna kawasan adat, tempat ibadah, tata guna lahan. Karakteristik budaya lanskap suku boti tediri dari jumlah penduduk desa suku boti Kecamatan Kie Kabupaten Timor Tengah Selatan- NTT Rekomendasi pengembangan wisata pada kawasan suku boti adalah preservasi.